Students' engagement in Distance Learning: creating a scenario with LMS and Social Network aggregation - Messias, Inês (2020)
Already a part of our daily lives, Web 2.0 is becoming also a part of Education, as it evolves to accompany society, education is becoming more personal, and with a focus on knowledge, reflection, social connection and engagement, as to include both digital natives and immigrants [1]. According to Siemens [2] today’s learning depends on connectivity among individuals and it tends to dissolve frontiers between formal and informal learning. This paper presents a study1, that aims to comprehend how an informal platform (such as Facebook) while complement of a formal platform (such as Moodle) can contribute to a greater engagement by the Higher Education level students’, as well as to measure the impact these tools can have on the knowledge acquisition process. Embedded on the Higher Education context, the study is centred in the levels of the students’ engagement and on the frequency and quality of their contributions in Forums, being its participants, lecturers and students of this level of education. Since it is objective of the study to understand how interaction and collaboration contribute to students’ involvement in elearning hybrid contexts the adopted theoretical framework is the Activity Theory, and the methodological approach chosen is of a mixed nature, using Social Network Analysis tools (SNA).